Comparative Results of Transurethral Incision with Transurethral Resection of The Prostate in Renal Transplant Recipients with Benign Prostate Hyperplasia - Sarier, Mehmet; Duman, Ibrahim; Kilic, Suleyman; Yuksel, Yucel; Demir, Meltem; Aslan, Mesut; Yucetin, Levent; Tekin, Sabri; Yavuz, Asuman Havva; Emek, Mestan (Urology Journal, 2018)
Purpose: The aim of this study is to compare the results of transurethral incision of the prostate (TUIP) and transurethral resection of the prostate (TURP) for the surgical treatment of benign prostate hyperplasia (BPH) in patients with renal transplantation. Materials and Methods: Between April 2009 and May 2016, BPH patients with renal transplants whose prostate volumes were less than 30 cm3 were treated surgically. Forty-seven patients received TURP and 32 received TUIP. The patients' age, duration of dialysis, duration between transplant and TURP/TUIP, preoperative and postoperative serum creatinine (SCr), International Prostate Symptom Score (IPSS), maximum flow rate (Qmax) and postvoid residual volume (PVR) were recorded. At 1-,6- and 12-month follow-up, early and long-term complications were assessed. Results were evaluated retrospectively. Results: In both groups, SCr, PVR and IPSS decreased significantly after the operation, while Qmax increased significantly (P < .001). There was no difference between the two groups in terms of increase in Qmax and decrease in IPSS, SCr and PVR (P = .89, P = .27, P = .08, and P = .27). Among postoperative complications, urinary tract infection (UTIs) and retrograde ejaculation (RE) rates were higher in the TURP group than the TUIP group (12.7% versus 6.2% and 68.1% versus 25%,respectively), whereas urethral strictures were more prevalent in the TUIP group (12.5% versus 6.3%). Conclusion: For the treatment of BPH in renal transplant patients with a prostate volume less than 30 cm3, both TUIP and TURP are safe and effective.